LITERASI KEUANGAN SYARIAH DAN KEPUTUSAN INVESTASI: ANALISIS SOSIAL DEMOGRAFI - Elfira Maya Adiba (IQTISHADUNA, 2021)
Islamic financial literacy is important because it has an influence on financial planning and investment decisions. This study aims to determine the Islamic financial literacy index of the people of Surabaya, the influence of socio-demographic factors on Islamic financial literacy, the influence of Islamic financial literacy on financial planning and investment decisions. The data analysis technique that used in this research is partial least square (PLS). The results of this study are demographic factors and education level have no effect on Islamic financial literacy. Sharia financial literacy also has no effect on financial planning. Another result is that Islamic financial literacy has a significant effect on investment decisions.